Combining science, education, and production as a way to form an effective mechanism for preventing climate change : collective monograph - Vnukova, N.; Prokopenko, N. (Харківський національний автомобільно-дорожній університет, 2024)
The collective monograph was prepared by researchers from the partner universities of the international ERASMUS+ project “Synergy of educational, scientific, managerial and industrial components for climate management and climate change prevention / CLIMAN” 619119-EPP-1-2020 -1-NL-EPPKA2-CBHE-JP. The publication highlights the results of our own research on the general issues and origins of global climate change, sectoral issues of sustainable development, the introduction of natural solutions, the application of innovative approaches to energy supply for the development of transport, agriculture and resource conservation. The monograph is intended for a wide range of readers who are interested in the problems of global climate change, as well as ways to prevent, adapt and minimize the effects of climate change.
Об’єднання науки, освіти, виробництва як шлях до формування дієвого механізму попередження змін клімату